Molecular Identification of Dominant Bacteria (16S rRNA) and Heavy Metal Contamination in Rono Dange, Central Sulawesi - Safriyanto S. Maruka; Nurfadilah (Postgraduate, University of Mataram, 2025)
Rono Dange is a traditional smoked anchovy product that has great economic value and potential as a local food. However, there are differences in quality, especially in terms of microbiology and food safety. This study aims to identify the dominant bacteria found in Rono Dange products and evaluate heavy metal contamination of lead (Pb), cadmium (Cd), and magnesium (Mg) as indicators of consumption safety. Rono Dange samples were obtained from five traditional processors in Lero Village and analyzed in the laboratory. Bacterial isolation and identification were performed using pure culture techniques, DNA extraction, 16S rRNA gene amplification using PCR, and DNA sequence analysis to determine the dominant species. Heavy metal content testing was performed using the AAS (Atomic Absorption Spectrophotometry) method in accordance with the SNI 7387:2009 standard. The results showed that the dominant bacteria found in the Rono Dange samples belonged to the genera Bacillus, Staphylococcus, and Pseudomonas, which play a role in the formation of the distinctive aroma but also indicate potential contamination if not properly controlled. The concentrations of Pb and Cd heavy metals in most samples were still below the SNI threshold, while Mg levels showed variations influenced by fuel and smoking duration. Overall, it was concluded that Rono Dange is still suitable for consumption, but it is necessary to standardize the smoking process and control the cleanliness of the production environment to ensure product quality and safety.